Influencia del tiempo de almacenamiento y tipo de cemento en la fluidez, fraguado y compresión de morteros de asiento - Alvarado Corcuera, Donaldo Alexis (2018)
In the research influence of the storage time of the 3 most used cements in the city of Trujillo, which will allow to know to engineers and construction masters the time which they can store their cement without reducing the properties of the mortars that are made with them, on the compressive strength, fluidity and time of setting of hydraulic cement; for this investigation was used fine aggregate of 2.4, and cements type ICo, type MS and type I, and dosages used were cement: sand 1:3 and 1:4, with a constant water/cement ratio of 0.75, the Cement was stored indoors within the campus of the National University of Trujillo with a relative humidity in air around of 88%, which was measured with a digital thermo-hygrometer. The mortar made with these cements was evaluated at different storage times of 5 days, 10 days, 15 days, 20 days, 25 days, 30 days, 35 days, 40 and 45 days. For the shaping and the compression test cubes of 5 cm x 5 cm x 5 cm were used under the norm ASTM C109 standard was used, to determine the setting time of the mortar the norm ASTM C191 standard was used and for the fluidity the norm ASTM C1437 standard. It was found that cement storage adversely affect in the behavior of the mortar on flowability, setting time and compressive strength. In the test of fluidity starts with a value of 100% and an increase is observed in the first days of storage of cements type ICo, type I and type MS getting a maximum point which is 117 %, 122 % and 124% at a storage time of 25 days, 20 days and 30 days around, later the fluidity to decrease, to 45 days of storage get a value of 79%, 85 % and 81% around. In the setting time test, the initial and final setting time tend to increase, the initial setting time of the standard samples are 93 minutes , 86 minutes and 76 minutes, for cements type ICo, type MS and type I around, and 45 days of storage these values increase to 135 minutes, 130 minutes and 99 minutes around, the final setting times of the standard samples were 330 minutes, 375 minutes and 360 minutes for cements type ICo, type MS and type I around, and at 45 days of storage these values increase to 420 minutes, 480 minutes y 435 minutes around. In the compressive strength test the resistance decreases as the storage time increases, the strength of the standard samples were 238, 229 and 212 kg / cm2 for Type I, Type MS and Type ICo cements around, and 45 days after storage resistance decreases to 105, 114 and 99k g/cm2 around.